THE ROLE OF WORK COMMITMENT AS A MEDIATOR OF LEADERSHIP WORKPLACE MOTIVATION ON TEACHER ACHIEVEMENT AT SMP NEGRI KOTA BATAM - Indah Mawarni; Ratih Anggraini; Agustinus Setyawan (RADJA PUBLIKA, 2025)
Teachers at State Junior High Schools in Batam City, Riau Islands Province, have varying work ethics. The varying performance of teachers is caused by education, training and experience gained while working. The problem in State Junior High Schools in Batam City is the less than optimal achievement of teachers. Based on the problem, it is suspected that there are several influencing factors, namely leadership, work place, motivation and work commitment felt by teachers. This study aims to analyze the mediating role of work commitment in the influence of leadership, work place, motivation on teacher achievement. The study was conducted using a quantitative descriptive method and analyzed using Structural Equation Modelling-Partial Least Square (SEM-PLS). The data used in this study used primary data obtained from the answers of 125 respondents. The results of this study support the proposed hypothesis, namely: Leadership has a positive and significant effect on Work Commitment. Motivation has a positive and significant effect on Work Commitment. Work Place has a positive and significant effect on Work Commitment. Work Commitment has a positive and significant effect on Teacher achievement. Work Commitment can mediate the positive and significant influence between leadership variables, work place and motivation simultaneously on teacher achievement in SMP Negeri Batam City. The managerial implication of this study is that the role of work motivation needs to be considered more deeply to improve teacher achievement to accomplish the targeted goals, because this variable has a positive and significant influence both directly and indirectly.